Main temple on Harsha Hill - Temples of India Project Team (Jio Institute, 2024)
The temple, which is in a ruinous condition, consists of a mulaprasada of tri-anga specification, joined by a rangamandapa. It lacks the pitha but starts from a single plinth-course. The vedibandha is damaged in some places but otherwise had a kumbha with intricate udgama motif and a small central box carrying a figure. The jangha, which is almost totally ruined, had dikpalas at the karnas, as evidenced by remains in the northeastern corner. The surasundaris were likely present at the pratirathas and the salilantara-recesses. Inside the sanctum is a shivalinga in active worship, seemingly contemporaneous with the main shrine. The temple lacks any superstructure, which could have collapsed over centuries since its construction. Stylistically, the architecture of the Harshnath Temple falls in the Maha-Maru style but exhibits several emerging Maru-Gurjara style elements, particularly evident in the base mouldings and other temple elements.